2020
DOI: 10.1111/acel.13147
|View full text |Cite
|
Sign up to set email alerts
|

PML2‐mediated thread‐like nuclear bodies mark late senescence in Hutchinson–Gilford progeria syndrome

Abstract: Progerin accumulation disrupts nuclear lamina integrity and causes nuclear structure abnormalities, leading to premature aging, that is, Hutchinson–Gilford progeria syndrome (HGPS). The roles of nuclear subcompartments, such as PML nuclear bodies (PML NBs), in HGPS pathogenesis, are unclear. Here, we show that classical dot‐like PML NBs are reorganized into thread‐like structures in HGPS patient fibroblasts and their presence is associated with late stage of senescence. By co‐immunoprecipitation analysis, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…This study also found that prelamin A accumulated at PML NBs following DNA damage. Importantly, PML NB deregulation was also observed in a study investigating the effect of progerin expression [60]. Progerin is associated with Hutchinson Gilford Progeria Syndrome (HGPS) and, like prelamin A is a permanently farnesylated lamin A precursor, but unlike prelamin A, it has a 50 amino acid deletion [61].…”
Section: Nuclear Actin Responds To a Myriad Of Dna Damage Lesions And...mentioning
confidence: 89%
“…This study also found that prelamin A accumulated at PML NBs following DNA damage. Importantly, PML NB deregulation was also observed in a study investigating the effect of progerin expression [60]. Progerin is associated with Hutchinson Gilford Progeria Syndrome (HGPS) and, like prelamin A is a permanently farnesylated lamin A precursor, but unlike prelamin A, it has a 50 amino acid deletion [61].…”
Section: Nuclear Actin Responds To a Myriad Of Dna Damage Lesions And...mentioning
confidence: 89%
“…The SAβ-gal staining reflects the activity and level of β-D-galactosidase encoded by Glb1 25 . Thus, we thought that coupling Glb1 transcription to an mCherry signal might avoid the subjective effects of SAβ-gal staining 27 and facilitate live-imaging analyses. Interestingly, the high GAC signal in MA mice points to cardiac hypertrophy, which might be one reason for the earlier mortality of GACH mice.…”
Section: Discussionmentioning
confidence: 99%
“…Glb1 +/m and wild-type MEF cells were isolated from embryos on day 13.5 of gestation. Primary normal human fibroblasts (HuFB) were isolated from the skin tissue of a healthy female donor 27 and the written informed consent was obtained from the donor. The use of human fibroblasts was approved by the Medical Ethic Committee of Shenzhen University.…”
Section: Cell Culturementioning
confidence: 99%
“…Primary normal human dermal fibroblasts isolated from a healthy female donor (aged 24 years) ( 42 ) and HGPS dermal fibroblasts HGADFN143 (HG143) ( 6 ) were described previously. MCF-7 (Michigan Cancer Foundation 7) cells, human embryonic kidney (HEK) 293T cells, HeLa cells, and MEFs were described previously ( 33 ).…”
Section: Methodsmentioning
confidence: 99%